Nematodos fitoparasitos en areas productoras de patata de motril y salobreña - Talavera, M.=700 1 Andreu, M.; Valor, H.; Tobar, A.
(Es, En)
ilus., 25 ref.
Keywords: GLOBADERA; NEMATODA; PAPA; MUESTREO; ESPAÑA; PATATA; PROSPECCION